Malaysian young adults attitude toward local and foreign made electronic and electrical products :the country origin effect - Ng, See Ying. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The main aim of this study was to determine whether there were significant difference s in Malaysian young adults a ttitude toward different countries’ country image, different countries made electronic and electrical products and its correspondence marketing activities. Besides, it intend ed to show the country of origin effect on their attitude as well as purchase beha viors (past experien ces). The scope of this study was limited to young adults aged from 20 to 29 years old in Kuala Lumpur, Malaysia. A total of 400 questionnaires were distributed and 389 filled questionnaires were analyzed due to 11 uncompleted questionn aires were found . The results of ANOVA showed that there were significant differences exist between variables. However, there was no significant difference between the independent variables and attitude toward marketing activities in term of price. Besides , the Spearman’s rho correlation analysis support ed t he ANOVA findings that there were significant and positive relationship s among independent variables and dependent variables. However, it showed that the relationship between independent variables with a ttitude toward marketin g activities in term of price was weak.